Solar-powered hybrid station with integrated liquid air and gaseous hydrogen energy storage for electric vehicle charging and hydrogen refueling - Nurettin Sezer (14778217) (2025)
This study presents the design and assessment of a solar-powered hybrid station by incorporating several energy conversion, storage, and recovery strategies to maximize system reliability, energy utilization, and efficiency. The system is powered by solar photovoltaic modules and integrated with liquid air and electrolytic hydrogen energy storage. The produced hydrogen is compressed and precooled to meet the requirements of fast refueling. The heat from hydrogen compression and excess heat from Liquid Air Energy Storage (LAES) discharge are recovered for additional power generation in a Trilateral Flash Cycle (TFC). The system is designed to fast refuel four fuel cell electric vehicles and fast recharge eight battery electric vehicles simultaneously. Thermodynamic calculations are performed to analyze the system in detail and a parametric study is conducted to investigate the effect of various parameters on system performance. The results indicate that the integrated system is promising to generate and store the required energy for the hybrid station. The efficiency of the PV, LAES, TFC, electrolyzer, and overall system is found to be 16 %, 57.1 %, 11.6 %, 56.7 %, and 55.5 %, respectively. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.151338